Pengaruh Gaya Kepemimpinan, Kerja Tim dan Budaya Keselamatan Pasien terhadap Pencapaian Sasaran Keselamatan Pasien (Patient Safety) di Rumah Sakit Umum Daerah Majalengka - Suparjo, Dede; Paramarta, Vip; Rulia, Rulia (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Patient safety is a patient's right. Patient safety is a priority for health services worldwide. Leadership, teamwork and patient safety culture are factors that have a major contribution to causing patient safety problems. This study aims to determine the effect of leadership style, teamwork and patient safety culture on the achievement of patient safety targets at the Majalengka Regional General Hospital. This research method is a descriptive and verification method. The nature of the data used in this study is quantitative and the sources of research data are primary and secondary data. The research sample was 78 respondents of the Majalengka Regional General Hospital. Data collection techniques were interviews using questionnaires. Data analysis used descriptive analysis and multiple regression analysis. The results showed that leadership style was in the good category, while teamwork, patient safety culture and achievement of patient safety targets were in the fairly good category. Leadership style, teamwork and patient safety culture simultaneously have a significant positive effect on the achievement of patient safety targets at the Majalengka Regional General Hospital. Majalengka Regional General Hospital should strengthen the role of leadership style by improving patient safety culture because this can improve patient safety performance in employees and increase teamwork solidity through improving patient safety culture because this can also improve patient safety performance; The Regional Government should propose the creation of programs or policies in building an organizational culture to improve patient safety performance and in the recruitment process prioritize the right leadership style, namely supporting increasing rewards in the form of increased incentives based on performance.